2020
DOI: 10.1038/s41375-020-0963-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of progression-free or event-free survival with overall survival in diffuse large B-cell lymphoma after immunochemotherapy: a systematic review

Abstract: To investigate progression-free survival (PFS) and event-free survival (EFS) as early efficacy endpoints in diffuse large B-cell lymphoma (DLBCL), this systematic review included phase III randomized controlled trials (RCTs), phase II trials, and retrospective studies in newly diagnosed DLBCL receiving rituximab-containing chemotherapy through databases search up to 2019. Quality control was performed, where studies with high risk of bias were excluded. Prediction models were first established using the RCTs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…Consistent with the present finding, the subsequent survival of patients with DLBCL or PTCL who achieved EFS24 or PFS24 is almost equal to that of the age-, sex-, and country-matched general population [26][27][28][29]32]. Furthermore, we have confirmed the association of PFS24 with OS in trial-and treatment armlevel in RCTs on DLBCL patients treated with immunochemotherapy; its association has been externally validated using the literature-based data from high-quality phase II and retrospective studies [40]. Similarly, in patients with follicular lymphoma and marginal zone lymphomas [39,41], early progression of disease within 24 months after initial treatment stratified subsequent OS and identifies a high-risk population.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the present finding, the subsequent survival of patients with DLBCL or PTCL who achieved EFS24 or PFS24 is almost equal to that of the age-, sex-, and country-matched general population [26][27][28][29]32]. Furthermore, we have confirmed the association of PFS24 with OS in trial-and treatment armlevel in RCTs on DLBCL patients treated with immunochemotherapy; its association has been externally validated using the literature-based data from high-quality phase II and retrospective studies [40]. Similarly, in patients with follicular lymphoma and marginal zone lymphomas [39,41], early progression of disease within 24 months after initial treatment stratified subsequent OS and identifies a high-risk population.…”
Section: Discussionsupporting
confidence: 88%
“…Event-free survival is a widely accepted, robust early efficacy end point in clinical trials involving patients with large B-cell lymphoma, on the basis of retrospective analyses of randomized trials that have shown a correlation between improvements in event-free survival and overall survival. [19][20][21] Patients with relapsed or refractory large B-cell lymphoma who do not have a response to salvage chemotherapy (i.e., who have progressive or stable disease) will not benefit from high-dose chemotherapy with autologous stem-cell transplantation. 22 In this scenario, a change to third-line therapy is indicated, sometimes in the absence of progressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…There has been debate on how a surrogate endpoint should be considered as valid. We employed the correlation approach which has been used to assess the possibility of PFS or TTP as a surrogate endpoint for OS in locally advanced NSCLC (11), nasopharyngeal carcinoma (8), and diffuse large B-cell lymphoma (10). Candidate surrogate endpoints could be valid only if the correlation coefficient was greater than 0.75 (55).…”
Section: Previous Meta-analyses Have Assessed Surrogate Endpoints Inmentioning
confidence: 99%
“…For example, crizotinib was approved for anaplastic lymphoma kinasepositive non-small-cell lung cancer on the basis of PFS (6) and sunitinib for gastrointestinal stromal tumor and renal cell carcinoma on the basis of TTP (7). PFS and TTP have also been demonstrated to be valid surrogate endpoints for OS in some malignancies (8)(9)(10)(11)(12). However, an early valid surrogate endpoint has never been reported in LS-SCLC patients.…”
Section: Introductionmentioning
confidence: 99%